Mono-, di- and trisubstituted derivatives of eflornithine: synthesis for in vivo delivery of DL-α-difluoromethyl-ornithine in plasma - Cloete, Theunis T; Johansson, Carl C; N'Da, David D; Vodnala, Suman Kumar; Rottenberg, Martin E; Breytenbach, Jaco C; Ashton, Michael (Arzneimittelforschung, 2011)
The aim of this study was to synthesize a series of mono-, di- and trisubstituted derivatives of the human African trypanosomiasis drug eflornithine (α-difluoro-methylornithine, DMFO, CAS 70052-12-9) to determine their partition coefficients, and to assess whether they deliver the parent drug in the plasma. If increased plasma concentrations of eflornithine could be achieved in this way, an oral dosage form would be possible. The derivatives, nine in total, were successfully synthesized by multi-step derivatisation of eflornithine on either its α-carboxylic or/and α-amino or/and 5-amino groups by either esterification or/and amidation or/and carbamylation, and their structures confirmed by NMR and MS spectroscopy. The majority of derivatives were more lipophilic than eflornithine with log D values in phosphate buffer solution (pH 7.4) ranging from −1.34 to 1.59 (vs. −0.98 for eflornithine). The in vivo absorption after oral administration to Sprague-Dawley rats showed that no derivative delivered eflornithine in the plasma, indicating that the derivatives were either not absorbed from the gastrointestinal tract or not metabolized to the parent drug. Two of the monosubstituted activities were toxic for T. brucei blood stream forms.
Keywords: α-Difluoromethylornithine; Eflornithine derivatives; Human African trypanosomiasis (HAT); Sleeping sickness; Trypanosoma brucei gambiense